Scaling Up Private Sector Financing for Climate Change Adaptation in Zimbabwe: A Brief Literature Review - Hlatshwayo , Edson; Qutieshat , Abubaker (International Journal of Humanity and Social Sciences, 2024)
Developing countries such as Zimbabwe that are highly vulnerable to climate change, are struggling to close the funding gap for climate change adaptation largely due to constrained fiscal space, and also the inadequate climate finance flows from developed countries. This article reviews the existing literature relevant to closing the climate finance gap in Zimbabwe through scaling up funding from the private sector funding. The literature shows that current private sector flows for climate finance are far below what is required to meet the needs of the country. The paper presents literature review findings, and also identifies solutions for unlocking more domestic private sector finance for climate change adaptation. The findings of the study contribute towards informing government policy on climate change particularly with regards to the mobilization of additional finance.